ALTERATIONS IN THE MICROBIAL LOAD AT CERTAIN NON-SPECIFIC IMMUNE SITES OF MACROBRACHIUM ROSENBERGII SUPPLEMENTED WITH CENTELLA ASIATICA - M. P. SALINI,; THOMAS , A. AKHILA; ANAND, JASMINE (The Bioscan, 2013)
Macrobrachium rosenbergii has been the focus of research in India in the past few years. As a negative impact to the success of aquaculture due to intensification lead to higher disease outbreaks. The bacterial diseases are the most common due to intensification. In the present study the Macrobrachium rosenbergii fed with diet containing medicinal plant, Centella asiatica to test the antimicrobial activity. The prawns were fed with diet containing C.asiatica (0.2%). After 4 months both control and the experimental prawns were examined for microbial flora. Isolation and identification were also done. The investigation showed a significant reduction in the pathogenic bacteria and also found an improvement in the probiotic bacteria in prawns fed with experimental diet containing C.asiatica than the control diet. The % survival is 75% in medicated diet, but it is only 40% in control diet. The medicated diet also showed improved growth parameters. The total microbial load at non-specific immune sites, such as gill, gut and exoskeleton of both control and medicated feed were examined after the experiment. The total microbial load at gill, gut,exoskeleton were 41.00 x 105,50.00 x 106,30.00 x 106 respectively in control feed, but total microbial load at gill, gut, exoskeleton were 34.00 x 105, 28.00 x 106, 22.00 x 106 respectively in medicated feed. Major pathogenic bacteria found in culture were Vibrio type I, Staphylococcus type III, Micrococcus type I, Strepto coccus I, Acinetobacter type I, Acinetobacter typeIII, Arthrobacter type I, Enterobacteriacea, Flavobacterium Vibrio type II, Strepto coccus II, Pseudomonas. After treating with medicated diet, diversity and intensity of microbial flora get reduced and culture of medicated diet also showed presence of probiotic bacteria such as Bacillus.